Amyloid and tau PET in cerebral amyloid angiopathy-related inflammation two case reports and literature review - Yang, Jhih-Yong; Chu, Yung-Tsai; Tsai, Hsin-Hsi; Jeng, Jiann-Shing (Frontiers in Neurology, 2023)
Background Cerebral amyloid angiopathy-related inflammation (CAA-ri) is a clinical syndrome characterized by MRI findings of amyloid-related imaging abnormalities-edema (ARIA-E) suggestive of autoimmune and inflammatory reaction and hemorrhagic evidence of cerebral amyloid angiopathy. The longitudinal variation of amyloid PET and its imaging association with CAA-ri are undetermined. Moreover, tau PET in CAA-ri has been rarely investigated. Method We retrospectively described two cases of CAA-ri. We provided the temporal change of amyloid and tau PET in the first case, and the cross-sectional finding of amyloid and tau PET in the second case. We also performed a literature review of the imaging features of amyloid PET in reported cases of CAA-ri. Results In the first case, an 88-year-old male presented with progressive consciousness and gait disturbances over 2 months. MRI showed disseminated cortical superficial siderosis. Amyloid PET prior to and after the CAA-ri revealed focally decreased amyloid load in the region of ARIA-E. In the second case, a 72-year-old male was initially suspected to have central nervous system cryptococcosis but later diagnosed with CAA-ri because of the characteristic MRI features and good response to corticosteroid treatment; a subsequent amyloid scan revealed positive amyloid deposition of the brain. Neither case suggested an association between the region of ARIA-E and higher amyloid uptake on PET before or after onset of CAA-ri. Our literature review revealed variable findings related to amyloid burden in post-inflammatory regions in previously reported CAA-ri cases with available amyloid PET. Our case is the first report of longitudinal changes on amyloid PET and show focal decreases in amyloid load after the inflammatory process. Conclusion This case series highlights the need to better explore the potential of longitudinal amyloid PET in the understanding of the mechanisms of CAA-ri.